Co-delivery of axitinib and PD-L1 siRNA for the synergism of vascular normalization and immune checkpoint inhibition to boost anticancer immunity - Liu, Yanhong; Gong, Liming; Feng, Jing; Xiao, Congcong; Liu, Chenfei; Chen, Bohan; Chen, Liqing; Jin, Mingji; Guan, Youyan; Gao, Zhonggao; Huang, Wei (Journal of nanobiotechnology, 2025)
Immune checkpoint inhibition (ICI) has become the mainstay of immunotherapy for the treatment of renal cell carcinoma (RCC). However, only a small portion of patients exhibit a positive response to PD-1/PD-L1 blockade therapy and the key reason is that RCC belongs to a vascular-rich tumor for promoting immunosuppression. Specifically, the dysfunctional tumor vasculature hinders effector T cell infiltration and induces immunosuppressive tumor microenvironment via the release of cytokine, which attenuates the therapeutic efficacy of ICI. Therefore, regulating abnormal tumor vasculature may be a promising strategy to overcome the immunosuppressive microenvironment and enhance ICI therapy. Here, we propose an NGR peptide-modified actively targeted liposome (Axi/siRNA @NGR-Lipo) to encapsulate the anti-angiogenic agents Axitinib and PD-L1 siRNA to promote tumor vasculature normalization and relieve immune evasion for enhanced anti-tumor immunotherapy. With NGR-mediated tumor homing and active targeting, Axi/siRNA @NGR-Lipo could act on tumor vascular endothelial cells to inhibit neo-angiogenesis, increase pericyte coverage and vascular perfusion, and normalize the structure and function of tumor blood vessels. Meanwhile, it also enhanced immune effector T cells and NK cells infiltration and reduced the proportion of immunosuppressive T cells including MDSC cells and Tregs, thus improving the tumor immunosuppressive microenvironment. Moreover, Axi/siRNA @NGR-Lipo reduced the expression of PD-L1 protein in tumor cells, restored the recognition and killing ability of cytotoxic T cells, and relieved immune evasion. As expected, Axi/siRNA @NGR-Lipo displayed superior anti-tumor and anti-metastatic efficacy in mice bearing RCC. Overall, this study demonstrated the important potential of regulating abnormal tumor vasculature to reshape the immunosuppressive microenvironment and boost ICI therapy, which represents a promising avenue for the synergistic anti-tumor with cancer immunotherapy.